Analisisa Head Losses pada Design Interconnection Pipe Sistem Reverse Osmosis PLTU 2 Labuan dan Keuntungan bagi Perusahaan - Hardiman Wahyu Hidayat; Althesa Androva; Muhamad Safi'i (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2026)
Water Treatment Plant is a water treatment unit into water that meets the requirements in accordance with the needs of the generating unit. In PLTU Banten 2 Labuan for water treatment plant has two main processes namely seawater pretreatment (purification) and reverse osmosis (purification). Reverse osmosis is a water purification process by providing hydrostatic pressure on the feed water so that it can penetrate permeable membrane cells and produce pure water. Inside the water treatment plant is primarily RO (primary primer RO). Catridge filters are used to filter impurities or particles contained in activated carbon filter water which can damage or block the membrane RO. While HPP Primary RO is used to drain raw water from catridge to primary RO. This Final Project is made based on the findings of field problems when the filter change at catridge A while at the same time pump ready to operate HPP primary RO B due to HPP primary RO A is damaged or is undergoing improvement and vice versa at the time of change of filter at catridge B pump ready to operate HPP primary RO A. Problems caused when the filter change in the catridge cause the production of demin water must be stopped because the reverse osmosis system must stop. For that in this case then I choose the title of Final Project "Designing Interconnection Pipe to add reliability Reverse Osmosis System in PLTU Banten 2 Labuan". With the addition of Interconnection Pipe aims to anticipate the reverse osmosis stop system when the filter change in the catridge and HPP repair RO. This will reduce the financial loss caused by the unit must be daerating (down load).